(untitled) (Acta Scientiarum. Agronomy, 2013)
The Noble Dendrobium orchid (Dendrobium nobile Lindl.) is an ornamental species usually propagated by leaf axillary shoots called “Keikes”, but cutting is possible although, many do not produce leaves or roots and eventually rot. To increase the proportion of successful stalk cuttings, two substrates were evaluated in the present study (gravel and a 1:1 tree-fern shredded trunk:palm seed mixture) in interaction with the application of nitrogen fertilizer (urea 2 g L-1) and a commercial leaf fertilizer made from kelp seaweed (“Kelpak” a 2 mL L-1). Only water was applied for the control treatment. The evaluated parameters included the proportion of successful cuttings, vigor, the proportion of rotten stalks, the number of roots/plant and root length/per plant. The gravel was found to be the best substrate for the rooting and/or shoot production (37.2% in average) of the cuttings. The application of urea or Kelpak induced vigor in the obtained plantlets, but the dosage required for a greater efficiency was not reached. The cuttings layered on gravel plus the application of urea at a concentration of 2 g L-1 was the most effective treatment, with 40.7% successful cuttings.